Grapari Information Technology Service Analysis of Telkomsel Salatiga Using ITIL V3 Domain Service Operation - Daniel Albert Santoso; Agustinus Wijaya (APTIKOM SUMSEL, 2020)
Parameters for the success of IT in a company or organization are IT services to users in order to support the fulfillment of the business goals of a company or organization. Therefore, information technology has become a major requirement for companies or organizations. Operating IT services in a company or organization cannot be without problems. To find out the extent to which IT services are running and the extent of management in managing and handling incidents and problems in IT service companies, an analysis and assessment of IT services is needed. This research proposes the ITIL framework version 3 (Information Technology Infrastructure Library) with the Service Operation domain to review IT service practices. The results of this study indicate several recommendations including increasing the number of resources who are experts in the IT field, so that any obstacles that arise in the application can be resolved immediately. It is hoped that by carrying out this research, GraPARI can reduce these obstacles and can work optimally.